Effects of Quetiapine on Novelty‐Related Object Recognition Memory and Hippocampal BDNF Level in Sleep‐Deprived Rats - Öznur Özge Özcan; Burcu Çevreli; Emel Serdaroğlu Kaşıkçı; Mesut Karahan; Muhsin Konuk (Brain and Behavior)
ABSTRACT Background The underlying mechanism of quetiapine (QET) in treating cognitive impairment in sleep deprivation is unclear. The present study aimed to evaluate the effects of treatment with QET on novel object recognition and hippocampal (hippo) brain‐derived neurotrophic factor (BDNF) levels in rats submitted to 72 h sleep deprivation (SD). Materials and Methods A total of 42 adult male Wistar albino rats were assigned into six experimental groups: non‐sleep‐deprived (NSD) control, short‐term control group (n = 7) received a single intraperitoneal (i.p.) injection 10 mg/kg QET of 1 mL saline (4 days) (NSD‐STQET), long‐term control group (n = 7) received single i.p. injection 10 mg/kg QET of 1 mL saline (30 days) (NSD‐LTQET); 72 h sleep‐deprived (SD) group, 72 h SD short‐term group received short‐term i.p. injection 10 mg/kg QET of either (n = 7) (SD‐STQET), and 72 h SD long‐term group received long‐term i.p. injection 10 mg/kg QET of either (n = 7) QET (SD‐LTQET). SD was performed using the modified multiple‐platform technique in a water tank for 72 h. Additionally, we aim to reveal the consequences of 72 h SD and QET effects on memory processes with hippo BDNF levels by testing rats in the novel object recognition (NOR) test and ELISA method. Results Long‐term QET administration in healthy rats decreased NOR and BDNF protein expression in the hippocampus, as did 72 h SD. Long‐ and short‐term QET administration reversed SD effects, but only short‐term QET administration increased hippo BDNF. Conclusion These results suggest that the beneficial effects of QET on SD may be partly related to the upregulation of recognition memory and neuroprotective proteins such as BDNF. However, long‐term QET treatment in the absence of a disease model may have the potential to negatively impact recognition memory and BDNF levels, which support synaptic plasticity and cognitive function.